Enfermedad pulmonar crónica en paciente masculino de 70 años de edad. - Mindiolaza Salazar, Moisés David (2020)
Chronic obstructive pulmonary disease (COPD) is a progressive disease characterized by a chronic limitation of airflow to the lungs causing difficulty breathing, chronic coughing, wheezing and excessive mucus, associated with an inflammatory reaction of the airway, as a result of many factors such as exposure to wood smoke, harmful particles, gaseous pollutants, and tobacco smoke which significantly affects the lives of those who suffer from this disease. We present the case of Mr. NN, 70 years old, who has been a smoker of 20 cigarettes a day, begins to present exacerbations that are accompanied by his disease that in years past has been detected but not treated or diagnosed in the right way is why we emphasize that it is taken into account the scales of Bode /Bodex to guide the professional in an appropriate treatment that allows the patient to integrate into society to maintain a better quality of life.